Optimization of Multi-layer Welding of Titanium Alloy - Yasin Mustafa, Ahmed; Khairul Saleh, Mohamed Sahari; Basim A., Khidhir; M., Ishak (Maxwell Scientific Organization, 2015)
Gas Tungsten Arc Welding GTAW process is a multi-input and output process in which the resultant joint strength is governed by both independent and combination of process parameters. The identification of suitable combination parameter is crucial to get desired quality of welded joint and hence, there is need for optimization of GTAW process to achieve a best result. The present work is based on the GTAW process parameters on multilayer welding of titanium alloy (Ti-6Al-4V). The design of experiment is done by response surface method to find the desired welding conditions for joining similar plates alloy material. Analysis of variance methods were applied to understand the GTAW process parameter. The considered parameters are filler diameter, welding current, welding speed and welding speed, while the desired output responses are heat input. From the results of the experiments, optimization is done to find optimum welding conditions of welded specimen to minimize the heat input by four welding pass is (5570 J/mm) and the total net heat input during welding for a GTAW procedure by four welding layers (3342 J/mm). In order to prevent structure changes especially for thick plates.